Pengembangan Modul Bimbingan Kelompok dengan Teknik Role Playing untuk Meningkatkan Kepercayaan Diri Siswa - Sulandari, Sisca; Rochani, Rochani; Handoyo, Alfiandy Warih (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research is motivated by the issue of a lack of self-confidence often experienced by teenagers in educational institutions, especially high school students, including those at SMA Negeri 19 Tangerang Regency. One effort to increase students' self-confidence is by providing group counseling services using the Role Playing technique. This study aims to develop a group counseling module with the Role Playing technique, which is expected to enhance students' self-confidence. The method used by the researcher is the research and development (R&D) method, utilizing the 4D development stages: define, design, development, and dissemination. The results of the feasibility test on the research product yielded an average score of 92.7%, categorized as "very good" or "highly feasible." Furthermore, the results of a limited trial involving 12 respondents from class X students at SMA Negeri 19 Tangerang Regency obtained an average score of 98.69%. Based on the trial assessment results, this falls into the "very good" category. In addition, the researcher obtained pre-test and post-test scores to calculate the N-Gain percentage score. The N-Gain percentage score obtained from this study was 58.3%, indicating that the provided service falls into the "quite effective" category. Therefore, it can be concluded that the development of a group counseling module with the Role Playing technique to improve students' self-confidence can serve as a guideline for BK (guidance and counseling) teachers and can be implemented by BK teachers or users.